Modelling & integration of advanced propulsion systems - Doulgeris, Georgios C. (Cranfield University, 2008)
This research study focuses on the design of advanced propulsion cycles, having as primary design goal the improvement on noise emissions and fuel consumption. In this context, a preliminary cycle design method has been developed and applied on four novel propulsion systems; ultra high bypass ratio, recuperated, intercooled-recuperated, constant volume combustion turbofans. The analysis has shown significant improvement in jet noise, and fuel consumption, as a result of high bypass ratio. Additionally, a comparison to future fuel-optimised cycle has revealed the trade-off between noise emissions and fuel consumption, where a reduction of ~30dBs in jet noise may be achieved in the expense of ~10% increase of mission fuel. A second aspect of this study is the integration of the propulsion system for improving fan noise. A novel approach is followed, by half-embedding the turbofan in the upper surface of the wing of a Broad Delta airframe. Such an installation aids in noise reduction, by providing shielding to component (fan) noise. However, it leads to significant inlet distortion levels. In order to assess the effect of installation-born distortion on performance an enhanced fan representation model has been developed, able to predict fan and overall engine performance sensitivity to three-dimensional distorted inlet flow. This model that comprises parallel compressor theory and streamline curvature compressor modelling, has been used for proving a linear relation between the loss in fan stability margins and engine performance. In this way, the design engineer can take into consideration distortion effects on off-design performance, as early as, at the stage of preliminary cycle design.